Maternal and fetal outcomes in pregnant women with hyperemesis gravidarum - Parihar, Sangeeta; Singh, Swatantar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hyperemesis gravidarum (HG) is associated with maternal weight loss, nutritional deficiencies, fluid and electrolyte abnormalities, which may lead to adverse fetal and maternal outcomes. The purpose of this study was to evaluate the relationship of hyperemesis gravidarum to maternal and foetal outcomes. Methods: A hospital-based prospective observational study was carried out. All patients with singleton pregnancy diagnosed as / history of hyperemesis gravidarum the current pregnancy was included in the study. The pregnant women with multiple pregnancy, molar pregnancy, presence of pre-gestational diabetes, pre-gestational hypertension, and other causes of nausea such as appendicitis and pyelonephritis were excluded from the study. Results: 36 pregnant women with prevalence rate of 3.28% have been found to be suffering from HG. Almost half (17, 47.22%) of the pregnant women with HG had age less than 25 years. The significant association (p-value: 0.0099) has been found between parity and smoking with HG. HG was significantly associated with low birth weight (p-value: 0.0133); small for gestational age (SGA) (p-value: 0.0316); APGAR score < 7 after 1 minute (p-value: 0.0060); and APGAR score <7 after 5 minutes (p-value: 0.0006). There is no association found between mode of delivery, gestational diabetes, and pregnancy-induced hypertension with HG. Conclusions: HG can adversely affect fetal as well as maternal, though not significant, pregnancy outcomes.